2015
DOI: 10.1186/s13012-015-0350-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the adoption of self-management solutions: an interpretive synthesis of the literature on stakeholder experiences

Abstract: BackgroundIn a research context, self-management solutions, which may range from simple book diaries to complex telehealth packages, designed to facilitate patients in managing their long-term conditions, have often shown cost-effectiveness, but their implementation in practice has frequently been challenging.MethodsWe conducted an interpretive qualitative synthesis of relevant articles identified through systematic searches of bibliographic databases in July 2014. We searched PubMed (Medline/NLM), Web of Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 88 publications
1
51
0
2
Order By: Relevance
“…The importance of how to further the treatment's significance in relation to, for example cost, motivational and social aspects has been stressed. 20 In the present study, the responders reported that it was difficult to find the time to do the jaw exercises in the middle of the day. This might be explained by a combination of stress at work and the fact that a majority of patients did not want to do the exercises among other people.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The importance of how to further the treatment's significance in relation to, for example cost, motivational and social aspects has been stressed. 20 In the present study, the responders reported that it was difficult to find the time to do the jaw exercises in the middle of the day. This might be explained by a combination of stress at work and the fact that a majority of patients did not want to do the exercises among other people.…”
Section: Discussionmentioning
confidence: 53%
“…There are many different factors that may influence a patient's acceptance and adoption of a self‐management regime. The importance of how to further the treatment's significance in relation to, for example cost, motivational and social aspects has been stressed . In the present study, the responders reported that it was difficult to find the time to do the jaw exercises in the middle of the day.…”
Section: Discussionmentioning
confidence: 63%
“…Individuals’ adherence to such changes varies with their perceived health locus of control, diabetes self‐efficacy and length of time with their type 2 diabetes diagnosis (Klinovszky, Kiss, Papp‐Zipernovszky, Lengyel, & Buzás, 2019). Facilitators and barriers to effective diabetes self‐management behaviours vary among individuals and can change over time (Harvey, Dopson, McManus, & Powell, 2015). To help individuals with type 2 diabetes mellitus develop and maintain effective self‐management regimens, it is essential we deepen our understanding of what guides their decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that psychosocial support, patient education programs, active participation of family members and healthcare providers lead to success of selfmanagement in patients. Harvey et al reported that patients perceived that lack of support and weakness in communication with clinicians did not encourage them to be good in sustaining selfmanagement (25).…”
Section: Discussionmentioning
confidence: 99%